Use of Continuous Friction Measurement Equipment to Predict Runway Condition Rating on Unpaved Runways. Issue 1 (2017) - Tingle, Jeb S.; Norwood, Gregory J.; Cotter, Brian
The objective of this research was to develop a correlation between the runway condition rating (RCR) and runway surface friction measurements for dry and wet unpaved runways supporting C-17 aircraft operations. To achieve this objective, flight tests were conducted with an instrumented C-17 on several unpaved runways of different soil types under a variety of surface moisture conditions. A trailer-based continuous friction measurement device was used to conduct continuous surface friction measurements along the runway immediately before and following each C-17 landing event. These data were used to correlate the runway surface friction values from the device to the RCR computed from aircraft performance data. An accurate prediction of RCR allows predictions of aircraft stopping performance under adverse weather conditions.